Pengajaran Kosa-Kata Bahasa Arab dengan Metode Inovasi dan Kreatif di Masjid Nurul Rohmah Kampung Dabatan Distrik Misool Selatan Kabupaten Raja Ampat - Juang Setiawan; Siti Jamila Soltief; Utna Ombaier; Raudatul Janna; Robi Hilmy Maulana; Rabea Rahakbauw; Yeni Wali; Nursyabila Tamrin; Putri Syamry; Rosmawati Wotheysen; Anisa Rumakat; Sandy Aulia Putri; Khatipah; Abdullah (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
Arabic is the primary language in Islamic teachings, serving as a means to understand the Qur’an, hadith, and various Islamic scholarly sources. However, teaching Arabic in remote areas still faces numerous challenges, particularly the lack of appropriate teaching methods for children and the limited introduction of Arabic vocabulary from an early age. This situation also occurs in Kampung Dabatan, South Misool District, where children generally learn to recite the Qur’an at home without being taught Arabic vocabulary. Consequently, the children had no basic knowledge of Arabic vocabulary before the learning program was implemented. This study aims to describe the innovation of teaching Arabic vocabulary through the singing method conducted at Nurul Rohmah Mosque. This research employs a qualitative method with a fenomenologis. Data were collected through observation, interviews, and documentation, then analyzed narratively. The results indicate that the singing method, supported by audio and visual media, can improve Arabic vocabulary mastery, enhance pronunciation, and foster motivation and enthusiasm for learning among children. Therefore, the singing method can be an effective and relevant alternative for teaching Arabic vocabulary in communities that have never received systematic Arabic instruction.